Peran Kinerja Tenaga Pendidik Pada Kualitas Pembelajaran Di TK Taman Widya I Surabaya - Sriwigati Wulandari Alvisha; Iswati Iswati; Anis Fitriyasari; Arief Widijatmoko (Global Leadership Organizational Research in Management, 2024)
This research wants to find out how "The Role of Educator Performance in Learning Quality" corresponds to the main problem raised, namely the Role of Educator Performance in Learning Quality at Taman Widya I Surabaya Kindergarten. The background for this research was that residents around the school said that the school produced many quality graduates. The aim of this research is to find out how the performance of teaching staff in the teaching and learning process can produce perfect learning quality. This research uses qualitative methods, with the subjects being teaching staff and guardians of Taman Widya I Kindergarten Surabaya. Data was obtained using interviews, observation and documentation, which was then analyzed descriptively qualitatively. The results of this research are: 1) The importance of the quality of learning in the teaching and learning process, 2) Teaching staff play a crucial role in determining the quality of learning and that an effective teaching and learning process requires qualified teaching staff, 3) Differences in approaches in the way Class A teachers teach and Class B teachers are adjusted to the students' age and educational level